Identifikasi Bakteri Pada Jajanan Di Sekolah Dasar Negeri 060908 Tegal Sari Mandala II Kecamatan Medan - Atikah Hanum; Annisa Annisa (JURNAL PANDU HUSADA, 2020)
Abstract: Foodborne disease is an illness caused by food or beverages that contain microorganisms or chemicals. One of the causes of foodborne diseases is snacks sold in schools. There are some bacterias that can cause foodborne disease such as Salmonella sp, Staphylococcus sp, Escherichia sp, and Shigella sp. This is a descriptive observational study, with cross-sectional design, using every sample from SDN 060809 Tegal sari Mandala II, Kecamatan Medan Denai. The result of this study is that there are many types of bacterias, such as Staphylococcus aureus, Escherichia coli, nterobavter sp, Proteus sp, and Aerobacter aerogens on snacks. Every sample taken from SDN060908 was found to contain bacterias, but didn't exceed the specified limit. The most common bacteria is Enterobacter sp.Keywords: Foodborne disease, identification of bacteria, snack, elementary school.